2000
DOI: 10.1155/2000/764721
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis among Aboriginal and Nonaboriginal Persons in British Columbia

Abstract: OBJECTIVE:To compare cases of tuberculosis (TB) diagnosed among aboriginal persons with a random sample of nonaboriginal persons diagnosed with TB, and evaluate the trends in rates of disease between both groups during the same period. DESIGN: A case-control study. SETTING: A provincial TB control program. PATIENTS AND METHODS: All patients with TB diagnosed among aboriginal persons in British Columbia between 1992 and 1996 were compared with control patients diagnosed during the same period. For each patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Studies from Canada and Australia have shown that indigenous or aborigines are at a higher risk of TB than the nonaborigines [136138]. Aborigines have a higher than average prevalence of predisposing risk factors for TB such as renal failure, diabetes, alcohol abuse, and smoking.…”
Section: Summary Of Specific Risk Factorsmentioning
confidence: 99%
“…Studies from Canada and Australia have shown that indigenous or aborigines are at a higher risk of TB than the nonaborigines [136138]. Aborigines have a higher than average prevalence of predisposing risk factors for TB such as renal failure, diabetes, alcohol abuse, and smoking.…”
Section: Summary Of Specific Risk Factorsmentioning
confidence: 99%
“…Previous studies have shown that indigenous or aboriginal people are at a higher risk of TB than nonaborigines [42], [43], [44]. Aborigines have a higher prevalence of predisposing risk factors for TB, such as diabetes, alcohol abuse, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The high association between latent infection and an increased risk of disease progression may result in a high TB burden caused by disease reactivation in this community [44]. In British Columbia, decreased rates of TB among aboriginal people have been produced by the expansion of DOT and chemoprophylaxis [42]. Thus, screening for latent TB and prophylactic therapy remain important tools for reducing the risk of progression to TB disease in high-risk communities.…”
Section: Discussionmentioning
confidence: 99%
“…These results, as well as the present study's reported rate of clustering (63%), confirm ongoing transmission in Aboriginal communities (Table 1). Explanations for the higher incidence of TB among Aboriginal communities have included the remoteness of communities, health worker shortages, housing and socioeconomic conditions, substance abuse, the prevalence of latent TB infection and, more recently, the impact of HIV coinfection (1,20,22,23).…”
Section: Discussionmentioning
confidence: 99%